2021
DOI: 10.3389/fgene.2021.752424
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study for Carcass Primal Cut Yields Using Single-step Bayesian Approach in Hanwoo Cattle

Abstract: The importance of meat and carcass quality is growing in beef cattle production to meet both producer and consumer demands. Primal cut yields, which reflect the body compositions of carcass, could determine the carcass grade and, consequently, command premium prices. Despite its importance, there have been few genome-wide association studies on these traits. This study aimed to identify genomic regions and putative candidate genes related to 10 primal cut traits, including tenderloin, sirloin, striploin, chuck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…In a study of the functions of the homologous genes of the FAM family (KIAA1409, KIAA1440, KIAA1447, KIAA1768, and KIAA1276), it was found that the phenotype and developmental defects in gene-targeted mice were caused by functional deletion of three of these five genes (Nakayama et al, 2006). FAM184B (KIAA1276) is located downstream of LCORL/NCAPG, which was found to be with bovine organ weight (An et al, 2018), bovine carcass body weight (Naserkheil et al, 2021), and chicken growth traits (Jin et al, 2015) in previous studies. IHH is a member of the hedgehog family and is mainly related to the development of bones, especially cartilage, and regulates the differentiation of cartilage in the growth of long bones (Lanske et al, 1996).…”
Section: Selected Loci For Donkey Body Heightmentioning
confidence: 99%
“…In a study of the functions of the homologous genes of the FAM family (KIAA1409, KIAA1440, KIAA1447, KIAA1768, and KIAA1276), it was found that the phenotype and developmental defects in gene-targeted mice were caused by functional deletion of three of these five genes (Nakayama et al, 2006). FAM184B (KIAA1276) is located downstream of LCORL/NCAPG, which was found to be with bovine organ weight (An et al, 2018), bovine carcass body weight (Naserkheil et al, 2021), and chicken growth traits (Jin et al, 2015) in previous studies. IHH is a member of the hedgehog family and is mainly related to the development of bones, especially cartilage, and regulates the differentiation of cartilage in the growth of long bones (Lanske et al, 1996).…”
Section: Selected Loci For Donkey Body Heightmentioning
confidence: 99%
“…SNPs identified in this region include FAM110B, UBXN2B, LOC101116841, SDCBP, and NSMAF. It has been reported that these SNPs are associated with meat and carcass traits such as adiposity, sensory and anatomical characteristics (Lee et al 2013;Li & Kim 2015;Li et al 2017;Hay & Roberts 2018;de las Heras-Saldana et al 2020;Naserkheil et al 2020;Srikanth et al 2020;Srivastava et al 2020;Takeda et al 2020;Naserkheil et al 2021;Xu et al 2021;Fonseca et al 2022); health traits such as resistance to temperature stress, mastitis, and diseases (Kommadath et al 2014;Chen et al 2015;Minuti et al 2015;Smith et al 2019;Deng et al 2020;Li et al 2020;Naserkheil et al 2020;Brunes et al 2021;Londoño-Gil et al 2021;Ruan et al 2021;Haire et al 2022); production traits such as growth, feed intake, and feed conversion (Weng et al 2016;Seabury et al 2017); reproductive traits such as female fertility and age at calving (Fortes et al 2012;Gaddis et al 2017;Mota et al 2017;Silva et al 2020;Oliveira et al 2021;Fonseca et al 2022) and appearance traits such as coat color (Senczuk et al 2020;Chhotaray et al 2021). Genomic regions and genes identified as under selection using iHS and ROH approaches have been associated with various ecological and economic traits in studies conducted on livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the NCAPG gene is an important candidate gene for mammalian body size growth traits in growth trait association analysis of horses, sheep and domestic donkeys and is involved in chromosome condensation and methylation [57][58][59][60]. The FAM184B gene has been found in previous studies to be associated with cattle carcass weight [61]. For the chicken growth traits in the study of Jinghai yellow chickens in China, the NCAPG, KCNIP4, LDB2 and FAM184B genes located in the 71.5-78.9 Mb region of GGA4 and near this region had important effects on the growth traits, which was consistent with this study.…”
Section: Genome-wide Association Analysis Of Growth Traitsmentioning
confidence: 98%